Analisis Penggunaan Frasa Instruksional Dalam Pembelajaran Bilingual di Sekolah Dasar - Azizi, Kurniawan; Andika, Fadhlu Dwi; Qamarudin, Ali; Gumelar, Cahyo; Lituhayu, Garini; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the form, structure, and strategy of instructional phrase usage by teachers in bilingual learning in elementary schools. The type of method used is descriptive qualitative research. The results show that teachers use instructional phrases in the form of simple imperative sentences, both in full English and mixed with Indonesian (code-mixing). The translanguaging strategy is the main approach used by teachers to adjust instructions to the students' level of understanding. Translanguaging is used in the form of bilingual repetition, meaning clarification, and context adjustment. This study concludes that the strategic use of instructional phrases in a bilingual context can improve students' understanding and engagement in learning.